Forming the environmental professional competence of future specialists in ship technical systems and complex operation - A. Yurzhenko; O. Kononova; Y. Bevzenko (Науковий вісник Мукачівського державного університету. Серія "Педагогіка та психологія")
The maritime industry contributes to pollution, including oil spills, air emissions (such as sulphur oxides and nitrogen oxides), and ballast water discharge, negatively impacting marine ecosystems. As the global maritime industry continues to move towards stricter environmental regulations, endorsed by the International Maritime Organisation’s (IMO) MARPOL Convention (which mandates the reduction of pollution from ships), and more sustainable practices, future ship engineers with environmental competence are crucially needed to meet the demands of the evolving industry. This study explored the use of e-learning facilitated by the LMS Moodle platform for future specialists in ship technical systems and complex operations, particularly in developing environmental professional competence during the Maritime English course. To achieve the research objective, a survey method was employed to collect and analyse information on the development of environmental professional competence among students during discussions in English for Specific Purposes (ESP) classes. The findings indicated that the use of e-courses on the LMS Moodle platform and e-learning through Zoom video conferences significantly contributes to the formation of professional competence among future seafarers. The combination of these technologies provided an interactive approach to learning, allowing students to access educational materials at a time convenient for them and actively participate in distance learning. This method fostered the development of independent work skills, critical thinking, and enhances understanding of specialised topics through interactive discussions and real-time exchange of ideas. The practical value of this research lies in its potential application by teachers when preparing lessons for English for Specific Purposes (ESP), literature, history, and other subjects